Numerical-Experimental Correlation of Interlaminar Damage Growth in Composite Structures: Setting Cohesive Zone Model Parameters. (13th October 2019) - Di Caprio, F.; Saputo, S.; Sellitto, A.
Abstract : Composite laminates are characterized by high mechanical in-plane properties while experiencing, on the contrary, a poor out-of-plane response. The composite laminates, indeed, are often highly vulnerable to interlaminar damages, also called "delaminations." One of the main techniques used for the numerical prediction of interlaminar damage onset and growth is the cohesive zone model (CZM). However, this approach is characterised by uncertainties in the definition of the parameters needed for the implementation of the cohesive behaviour in the numerical software. To overcome this issue, in the present paper, a numerical-experimental procedure for the calibration of material parameters governing the mechanical behaviour of CZM based on cohesive surface and cohesive element approaches is presented. Indeed, by comparing the results obtained from the double cantilever beam (DCB) and end-notched flexure (ENF) experimental tests with the corresponding numerical results, it has been possible to accurately calibrate the parameters of the numerical models needed to simulate the delamination growth phenomenon at coupon level.